2012
DOI: 10.1128/mmbr.05027-11
|View full text |Cite
|
Sign up to set email alerts
|

Subversion of Host Recognition and Defense Systems by Francisella spp

Abstract: SUMMARY Francisella tularensis is a Gram-negative intracellular pathogen and the causative agent of the disease tularemia. Inhalation of as few as 10 bacteria is sufficient to cause severe disease, making F. tularensis one of the most highly virulent bacterial pathogens. The initial stage of infection is characterized by the “silent” replication of bacteria in the absence of a significant inflammatory response. Francisella achie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
151
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 125 publications
(153 citation statements)
references
References 244 publications
(367 reference statements)
2
151
0
Order By: Relevance
“…holarctica strains showed differences in the resistance of the strains to serum killing and among the hosts' susceptibility (Fig. 1), in conformity with previous observations (Jones et al, 2012). In tularaemia and intracellular bacteria research, a frequently used experimental infection model is the mouse infected with F. tularensis ssp.…”
Section: Resultssupporting
confidence: 68%
See 3 more Smart Citations
“…holarctica strains showed differences in the resistance of the strains to serum killing and among the hosts' susceptibility (Fig. 1), in conformity with previous observations (Jones et al, 2012). In tularaemia and intracellular bacteria research, a frequently used experimental infection model is the mouse infected with F. tularensis ssp.…”
Section: Resultssupporting
confidence: 68%
“…holarctica strain LVS has been described in humans (Nasr and Klimpel, 2008). However, the exact mechanism of this binding has not been discovered yet, but fibrinogen and/or plasmin are hypothesised to have a promoter role in fH binding to F. tularensis cell surface (Crane et al, 2009;Jones et al, 2012). Although in the present study host-pathogen interactions were observed by complement sensitivity assays, further examinations on fH binding to bacterial cell membrane proteins using Western blot assays did not reveal specific interactions in any of the animal species examined (Fig.…”
Section: Resultsmentioning
confidence: 40%
See 2 more Smart Citations
“…novicida is capable of causing disease in a number of mammalian species, including humans (12)(13)(14). During infection, F. novicida must resist the action of numerous antimicrobials that are present on mucosal surfaces and within phagosomes of innate immune cells such as macrophages (15). Compared with…”
mentioning
confidence: 99%